Chirality‐Driven Transportation and Oxidation Prevention by Chiral Selenium Nanoparticles. Issue 11 (23rd January 2020) - Huang, Yanyu; Fu, Yuanting; Li, Mengting; Jiang, Dawei; Kutyreff, Christopher J.; Engle, Jonathan W.; Lan, Xiaoli; Cai, Weibo; Chen, Tianfeng
Abstract: The chirality of nanoparticles directly influences their transport and biological effects under physiological conditions, but the details of this phenomenon have rarely been explored. Herein, chiral GSH‐anchored selenium nanoparticles (G@SeNPs) are fabricated to investigate the effect of their chirality on their transport and antioxidant activity. G@SeNPs modified with different enantiomers show opposite handedness with a tunable circular dichroism signal. Noninvasive positron emission tomography imaging clearly reveals that 64 Cu‐labeled l ‐G@SeNPs experience distinctly different transport among the major organs from that of their d ‐and dl ‐counterparts, demonstrating that the chirality of the G@SeNPs influences the biodistribution and kinetics. Taking advantage of the strong homologous cell adhesion and uptake, l ‐G@SeNPs have been shown here to effectively prevent oxidation damage caused by palmitic acid in insulinoma cells. Abstract : From benchtop to bedside? Selenium nanoparticles decorated with glutathione enantiomers (l ‐, d ‐, and dl ‐forms) display distinct biodistributions in mice as determined by PET imaging with 64 Cu‐radiolabeling. One extrapolation of this selectivity is that l ‐G@SeNPs prevent palmitic acid caused oxidative damage by facilitative uptake into insulinoma cells.